Reconstruction of Political Party Membership In the Indonesian House of Representatives - Cahyawati, Dwi Putri; Saragih, Bintan (Jurnal Cita Hukum, 2020)
Abstract:The House of Representatives (DPR) is an embodiment of the provisions of Article 1 Paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Sociologically, the existence of the DPR as people's representatives is a mandate from all Indonesian people that must be carried out. In Indonesian constitutional practice, the role of the DPR as a people's representative institution is manifested in the form of a faction, which is an extension of the political parties and DPR institutions. The faction was formed to optimize the functions, duties, and powers of the DPR. This study uses a qualitative research method with a statutory approach. The data recorded is the result of the author's research in the form of literature collection and interviews with several related parties. The results showed that the membership of political parties in the DPR towards the existence of the DPR as the implementer of the people's sovereignty did not show any connection between one another. The existence of political party membership and DPR membership are two different things that have no juridical relevance.Keyword: DPR, Political Party, General Election Abstrak:Dewan Perwakilan Rakyat (selanjutnya disebut DPR) merupakan lembaga perwakilan rakyat, yang merupakan perwujudan dari ketentuan Pasal 1 Ayat (2) Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Secara sosiologis keberadaan DPR sebagai wakil rakyat merupakan amanat dari seluruh rakyat Indonesia yang harus dijalankan. Dalam praktek ketatanegaraan Indonesia, peran DPR sebagai lembaga perwakilan rakyat diwujudkan dalam bentuk fraksi, yang merupakan perpanjangan tangan partai politik dan lembaga DPR. Fraksi dibentuk dengan maksud untuk mengoptimalkan   fungsi, tugas, dan wewenang DPR. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan peraturan perundang-undangan. Data yang didata merupakan hasil riset penulis dalam bentuk pengumpulan literature dan wawancara kepada beberapa pihak terkait. Hasil penelitian menunjukan bahwa keanggotaan partai politik di DPR terhadap eksistensi DPR sebagai pelaksana kedaulatan rakyat ternyata tidak menunjukkan adanya keterkaitan antara satu dengan yang lain. Adanya keanggotaan partai politik dan keanggotaan DPR merupakan dua hal berbeda yang tidak memiliki relevansi secara yuridis.Keyword: DPR, Partai Politik, Pemilu Аннотация:Палата представителей - это учреждение представителей народов, которое является реализацией положений в статьях 1 пункт (2) Конституции государства Республики Индонезии от 1945 года. Существование DPR в качестве представителя народа является социологически мандатом от всего народа Индонезии, который должен быть выполнен. В практике государственного управления в Индонезии, роль DPR как учреждения представителя народов проявляется в виде фракции, которая является продолжением политических партий и DPR. Фракция была сформирована с целью оптимизации функций, обязанностей и полномочий DPR. Данное исследование использует качественный метод с подходом нормативных актов. Полученные данные являются результатом исследования автора в виде сбора литературных материалов и интервью с несколькими связанными сторонами. Результаты исследования показали, что не существует какой-либо связи между членством в политической партии в DPR и наличием DPR как исполнителем суверенитета народов. Членство в политической партии и членство в DPR это две разные вещи, которые не имеют отношения к юридической стороне.Ключёвые Слова: DPR, Политическая Партия, Всеобщие Выборы